Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/jacs.0c07103
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions Accelerating Water Oxidation Catalysis via Intercatalyst O–O Coupling

Abstract: Intercatalyst coupling has been widely applied in the functional mimics for binuclear synergy in natural metal enzymes. Herein, we introduce two facile and effective design strategies, which facilitate the coupling of two catalytic units via electrostatic interactions. The first system is based on a catalyst molecule functionalized with both a positively charged and a negatively charged group in the structure being able to pair with each other in an antiparallel manner arranged by electrostatic interactions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…However, considering the complexity of the synthesis of multinuclear structures, non-covalent assembly strategies seem more attractive. Many reported works have emphasized the role of secondary interactions in intercatalyst coupling, as shown in Figure , such as π–π interaction, , electrostatic interaction, off-set interaction, etc. We envisage that those non-covalent interactions between the axial ligands can be expanded to hydrophobic interactions by replacing the substituents of axial ligands.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the complexity of the synthesis of multinuclear structures, non-covalent assembly strategies seem more attractive. Many reported works have emphasized the role of secondary interactions in intercatalyst coupling, as shown in Figure , such as π–π interaction, , electrostatic interaction, off-set interaction, etc. We envisage that those non-covalent interactions between the axial ligands can be expanded to hydrophobic interactions by replacing the substituents of axial ligands.…”
Section: Introductionmentioning
confidence: 99%
“…19a-c). 98 The authors found that water oxidation using either a Ru-dba catalyst containing both cationic and anionic charges (Fig. 19a) or a mixture of a Ru-dba catalyst containing two cationic charges with a Ru-dba catalyst containing two anionic charges (Fig.…”
Section: Intermolecular Electrostatic Interactions In Homogeneous Sys...mentioning
confidence: 99%
“…and (c) may be used to ease the formation of the pre-reactive dimer complex. 98 for the resulting cupric aqua complexes were measured in both organic and aqueous media, and the complex containing cationic charges in the secondary coordination sphere was found to have slightly stronger O-H bonds than the complex containing anionic charges in the secondary coordination sphere (91-91.5 kcal mol À1 vs. 87-91 kcal mol À1 respectively). Despite the modest increase in the thermodynamic driving force for hydrogen atom abstraction by the Cu III -OH complex containing cationic charges, the kinetics for HAT with this complex were over two orders of magnitude slower than that of the Cu III -OH complex containing anionic charges.…”
Section: Intermolecular Electrostatic Interactions In Homogeneous Sys...mentioning
confidence: 99%
“…The use of oriented internal electrostatic fields for impacting the binding, 1-3 activation, 1,2,4-8 and reactivity 7,[9][10][11][12][13][14][15][16] of small molecules is a rapidly emerging method for tuning the physical and chemical properties of metal complexes. 17,18 Internal electrostatic fields can be introduced into metal complexes either through incorporation of charged functional groups into ligands or through positioning of outer sphere ions, and they have been shown to be impactful in both ground state and catalytic contexts.…”
Section: Introductionmentioning
confidence: 99%